Two new species of Sisyrinchium (Iridaceae) from Subtropical Highland Grasslands of Southern Brazil - Aita, Adriana M.; Chauveau, Olivier; Souza-Chies, Tatiana T.; Eggers, Lilian (Phytotaxa, 2013)
Sisyrinchium antemeridianum and S. flabellatum are two new species of Sisyrinchium sect. Hydastylus that occur in the high altitude grasslands of Southern Brazil, in the states of Rio Grande do Sul and Santa Catarina. Sisyrinchium antemeridianum can be distinguished from similar species by the conspicuous rhizome with remnants of old leaves and flowers with larger tepals and longer, connate filaments. Sisyrinchium flabellatum has a distinctive equitant phyllotaxis and a lax inflorescence of numerous flowers with small, typically reflexed tepals. Both species are endemic to the Highlands of Southern Brazil. Morphological descriptions, illustrations and ecological information for both plants are presented.